First record of males of the invasive eucalyptus pest species Leptocybe invasa Fisher & LaSalle, 2004 (Hymenoptera: Eulophidae: Tetrastichinae) from South America - Aquino, Daniel Alejandro (2019)
The “blue gum chalcid”, Leptocybe invasa is a pest of eucalyptus worldwide. It has an Australian origin and has expanded into Asia, Europe, Africa and America. L. invasa females were reported from South America in the last decade. Thelytokous parthenogenesis is the most common reproductive mechanism of this pest. However, male adults have been reported from Asia and Southeastern Europe. In this work, L. invasa males are reported for the first time from South America (Argentina) and information on morphological characters of males is provided. The importance of this discovery is highlighted based on recent studies that suggested the existence of two cryptic Leptocybe species in invasive populations.